Impact of drug addiction on social environment focused in Mymensingh district (Research in Agriculture Livestock and Fisheries, 2015)
The study was carried out to assess the impact of drug addiction on social environments in 6 wards of Mymensingh town. Information were collected on age, education level, reason of drug use, sources of drug, occupation, types of drugs, time and place of drug use, marital status and side effect of drug use. The findings revealed that about half of the drug addicted were aged more than 30 years, two-fourth people was aged between 25-30 years following less than 25 years aged people. Among the drug addicted respondents 10% were illiterate, 31, 26, 13 and 18% respondents were educated up to primary, SSC, HSC and Graduate level respectively. Most of the drug addicted respondents took drugs at day time (55%), 34% at night, among them 55% preferred alcohol, 26% preferred Yaba, 13% Gaza, and 5% preferred yrap. About 36% drug addicts suffered from vomiting, 28%, 15% suffered from vertigo, headache and gastric respectively. Most of them (80%) faced different abnormalities in their working life. Among local people who were affected by drug addiction 45% were grocery shopkeeper, 36%, 18% were confectionary worker and tea stall owner respectively. The reasons determined through research, 63% affected people informed that drug addicts were involved with drugs from depression. The study revealed that drug addiction was worsening social environment of the study area. Several ways have been recommended to remove the curse of drug addiction from our country and Mymensingh district in particular. It will also assist responsible authority to take necessary measures against drug addiction.Res. Agric., Livest. Fish.2(3): 411-417, December 2015